Co-integration and causality analysis between stock market prices and their determinates in Jordan - Bekhet H.A.; Matar A. (2023)
The current study examines the short- and long-term equilibrium relationship between the stock price index (SPI) and the macroeconomic variables in Jordan. Annual time series data over the 1978-2010 period for industrial production (IP), money supply (M2), exchange rate (EX), and discount rate (DR) were used. The ADF, bound testing approach, CUSUM, and CUSUMQ tests were applied to test the stationary and co-integration among variables. The results suggest the existence of a long-term equilibrium relationship between SPI and the macroeconomic variables (i.e., IP, M2, EX, and DR). 2013 Elsevier B.V.